Sistem Dan Prosedur Penggajian Dan Pengupahan Pada Cv. Mitra Jaya Abadi (Laporan Kegiatan Kuliah Kerja Lapangan) - Mahira Nur Alfiani; Diana Zuhro; Sutini Sutini; Tjandra Wasesa; Wiratna Wiratna; Heri Toni (Universitas 45 Surabaya, 2023)
The issue of salary and wages always receives great attention from every employee, because salaries and wages are a source of income whose receipts are obtained from the education and skills he has during work. Salary and wage expenditure is very important because employees are very sensitive to errors in improper payroll so that it is good for salaries to be paid on time to be able to maintain a good working atmosphere. However, there are often problems in the company related to the provision of salaries and wages, such as employee salaries that are not paid on time and abuse by certain parties so that fraud and misappropriation arise that result in losses to the company. So the company cannot be arbitrary in the payment of salaries and wages, so the company provides a good control system for the payroll and wage system that is useful for improving employee welfare by using internal supervision on salaries and wages. In the company, one of the systems that supports company activities in handling transactions and activities related to salaries and wages is the payroll and wage accounting information system. The application of payroll and wage accounting information systems in a company can help management in managing labor costs that are neatly arranged and organized. The accounting information system in payroll and payroll describes a computerized recording system to record in the form of a flowchart flow section.